2015
DOI: 10.1111/nhs.12234
|View full text |Cite
|
Sign up to set email alerts
|

Gait velocity and walking distance to predict community walking after stroke

Abstract: Gait speed and walking distance were evaluated as predictors for levels of community walking after stroke. In this study, 103 stroke survivors were identified as limited (n = 67) or independent community walkers (n = 36). Ten meter and six min walk tests were used to measure gait speed and walking distance, respectively. The discriminative properties of gait speed and walking distance for community walking were investigated using receiver operating characteristic curves. Cut-off values of 0.87 m/s for communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…One study has reported that cutoff value of above 0.85 m/s and 318 m could predict community walking after stroke [36]. According to that study, patients with similar stage as in our study could walk at speed of 0.72 m/s [36]. Stroke patients with decreased SMI and hand grip strength in our study could walk at speed of 0.65 m/s.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…One study has reported that cutoff value of above 0.85 m/s and 318 m could predict community walking after stroke [36]. According to that study, patients with similar stage as in our study could walk at speed of 0.72 m/s [36]. Stroke patients with decreased SMI and hand grip strength in our study could walk at speed of 0.65 m/s.…”
Section: Discussionsupporting
confidence: 70%
“…It has been shown that gait speed is an important measure in comprehensive geriatric assessment [35]. One study has reported that cutoff value of above 0.85 m/s and 318 m could predict community walking after stroke [36]. According to that study, patients with similar stage as in our study could walk at speed of 0.72 m/s [36].…”
Section: Discussionsupporting
confidence: 57%
“…Such measures do not directly account for the safety, endurance, or tolerance of the participant, nor do they measure whether an individual actually participates in walking activities in their home or community. However, self-paced walking speed is one of the most common measures evaluated after a stroke and has been shown to predict community ambulation (38,39). Various speed thresholds have been proposed to distinguish home and community ambulators, ranging from 0.4-0.93 m/s (22,38); our selection of a 0.8 m/s threshold is on the higher end of this range.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of progress in rehabilitation is of utmost importance. For post-stroke rehabilitation, there are numerous standardised clinical measures predominantly assessing temporal and spatial gait parameters, e.g., 10-m walk test [ 1 , 2 ], 2-, 6-, and 12-min walk tests [ 2 , 3 ], up and go test [ 4 ], cadence [ 5 ] or step length symmetry [ 6 ]. Furthermore, the concept of minimal clinically important difference (MCID) is currently at the centre of a newer approach in research on clinical measures post-stroke [ 7 ].…”
Section: Introductionmentioning
confidence: 99%